Fallout: the psychosocial harms of negative military discharge experiences - Grant, Cameron; Woodyatt, Lydia; Bowen, Henry; Lane, Jonathan (Frontiers in Psychology, 2025)
Military discharge marks a pivotal life transition, often resulting in loss of identity, purpose, and belonging. Negative discharge experiences are further associated with feelings of institutional betrayal. This study explored which aspects of discharge negatively impact veterans during and after their transition. Using Reflexive Thematic Analysis on accounts from Australian veterans (N = 313), three key themes emerged: (1) Discharge Experiences as Institutional Transgressions and Betrayal, with sub-themes: Unceremonious Exits and Lingering Discharges, Left Harmed and Rejected, and Bad Actors and Acutely Harmful Events; (2) Discharge as a Loss of Self; and (3) Negative Discharge Experiences as Negative Centralizing Events and ‘Stuck-Points’. Findings revealed that veterans experience harm when they perceive their discharge as an institutional or personal transgression—ranging from bureaucratic disregard to service-related injuries leading to rejection and overt betrayal by bad actors. These events, regardless of severity, undermine veterans’ shared military identity and values, posing a psychological threat to their sense of belonging, severing familial-like bonds, and fostering feelings of rejection, diminished self-worth, isolation, and betrayal—hindering transition and identity reconstruction. We argue that the harm stems not from discharge itself but from veterans experiencing these negative experiences as a violation of shared values—values they were required to embody for group membership. In identity-centric workplaces like the military, where enculturation fosters deep, family-like bonds, discharge represents a unique psychosocial hazard. Proactive management is essential to mitigate lasting psychological harm.